Critical Investigation of the CD14 Promoter Polymorphism: Lack of a Role for In Vitro Cytokine Response and Membrane CD14 Expression - von Aulock, Sonja (American Society for Microbiology, 2005)
Blood of volunteers, genotyped for the CD14 C(−159)→T polymorphism, showed no difference in cytokine release when stimulated with nine CD14-dependent immune stimuli. An analysis of the published data on the proposed association of CD14 genotype with membrane CD14 density revealed no significant correlation, questioning a functional impact of the CD14 polymorphism.